2004
DOI: 10.1021/jf048777p
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Triterpenoid Antioxidants from Origanum majorana L. Herb and Extracts Obtained with Different Solvents

Abstract: Antioxidant properties of marjoram (Origanum majorana L.) herb and extracts obtained with ethanol, n-hexane, and supercritical CO2 extraction are presented. Individual antioxidants, ursolic acid, carnosic acid, and carnosol, were quantified with high-performance liquid chromatography. The effects of different parameters (temperature and pressure) of high-pressure extraction on the yield of carnosol were studied. Furthermore, two marjoram herbs from Hungary and Egypt were compared measuring hydrogen-donating ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 28 publications
0
55
0
2
Order By: Relevance
“…Marjoram has a strong antioxidant activity due to its high polyphenolic content (Hossain et al, 2010). Phenolic compounds isolated from marjoram herb include rosmarinic acid, ursolic acid, carnosic acid and carnosol, which possess free radical scavenging properties (Vagi et al, 2005). The antioxidant activity of phenolics is mainly due to their redox properties which allow them to act as reducing agents, hydrogen donors, singlet oxygen quenchers and metal chelators (Rice-Evans et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Marjoram has a strong antioxidant activity due to its high polyphenolic content (Hossain et al, 2010). Phenolic compounds isolated from marjoram herb include rosmarinic acid, ursolic acid, carnosic acid and carnosol, which possess free radical scavenging properties (Vagi et al, 2005). The antioxidant activity of phenolics is mainly due to their redox properties which allow them to act as reducing agents, hydrogen donors, singlet oxygen quenchers and metal chelators (Rice-Evans et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The botanical species selected in this research have in common a high content of antioxidants and phenolic compounds with essential properties such as flavonoids, terpenoids (carotenoids and xanthophylls), chlorophyll and ascorbic acid (Lee et al 2005;Vági et al 2005;Lubbe and Verpoorte 2011). These compounds can be extracted from the cell via the liquefaction of plant tissues to obtain a homogeneous vegetal extract rich in biochemical compounds.…”
Section: Resultsmentioning
confidence: 99%
“…It is most likely that these could be bioactive components. But the antioxidant potential of terpenoids, 23,24 quinones, 25 steroids, 26 and Chromone derivatives 27 has also been demonstrated in various studies and these classes of compounds are identified in the screened extracts. There are several reports where plants rich in terpenes and phenolics are used as food additives owing to their antioxidant and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 98%